Effects of cement, different bentonite, and aggregates on plastic concrete in Besh-Ghardash Dam, Iran - Kazemian, Sina; Ghareh, S. (AMER SOC TESTING MATERIALS, 2017)
Besh-Ghardash Dam is located 5 km from Bojnourd city in North Khorasan Province, Iran. This research investigated the use of a plastic concrete. Because of a lack of specified standards for such materials, there is a serious need to evaluate effects from the amount and the quality of concrete aggregates (fine and coarse gravel and sand), cement, water, and bentonite on mechanical properties. This study looked at the effect of the ratio of mixture proportions and cement, as well as the materials' quality, such as the type of bentonite on compressive strength, modulus of elasticity, and permeability of plastic concrete. The results showed that by decreasing the ratio of term activity in bentonite reduced compressive strength, because of an increase in free water when other components were held stable. The effect of the cement has a direct effect on elastic modulus, as well as the compressibility of plastic concretes. The results showed that there is a direct effect of the cement on the permeability of such plastic concrete.